2016
DOI: 10.1016/j.jvs.2016.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Results from the Multicenter Study on Aortoenteric Fistulization After Stent Grafting of the Abdominal Aorta (MAEFISTO)

Abstract: Late AEFs rarely occur during EVAR follow-up, but the risk is significantly increased when EVAR is performed for PSA after previous aortic surgery and EVAR is performed as an emergency. Conservative and surgical treatment of post-EVAR AEF are both associated with high mortality. However, beyond the perioperative period, surgical correction of AEFs appears to be durable at midterm follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(77 citation statements)
references
References 36 publications
2
70
1
4
Order By: Relevance
“…To achieve sufficient exposure of the vessel and guarantee an appropriate debridement, supravisceral clamping is mandatory in cases of aorto-enteric fistula, as already described by other groups. 17,18 However, in this study the presence of an aortoenteric fistula did not lead to higher mortality rates; in contrast other authors found this to be a risk factor for post-operative mortality. 18 Different grafts have been used for reconstructions after aortic graft infection; rifampicin soaked grafts have been well described and evaluated in large series as the preferred treatment option.…”
Section: Discussioncontrasting
confidence: 79%
“…To achieve sufficient exposure of the vessel and guarantee an appropriate debridement, supravisceral clamping is mandatory in cases of aorto-enteric fistula, as already described by other groups. 17,18 However, in this study the presence of an aortoenteric fistula did not lead to higher mortality rates; in contrast other authors found this to be a risk factor for post-operative mortality. 18 Different grafts have been used for reconstructions after aortic graft infection; rifampicin soaked grafts have been well described and evaluated in large series as the preferred treatment option.…”
Section: Discussioncontrasting
confidence: 79%
“…110 In a multicentre study, an AEnF occurred in 32 patients (0.08%). 133 EVAR after anastomotic postsurgical pseudoaneurysm was significantly associated with developing an AEnF.…”
Section: Classmentioning
confidence: 95%
“…The MAEFISTO study (multicenter study on aortoenteric fistulization after stent grafting of the abdominal aorta) evaluated 3932 endograft implantations from 1997 to 2013 and reported an incidence of AEF development after EVAR of 0.46% for atherosclerotic aneurysmal disease and 3.9% when performed for postoperative pseudoaneurysm. 5 …”
Section: Discussionmentioning
confidence: 99%